In Need of God: Mozart, Faith, and Così fan tutte - Lösel, Steffen (Theology today, 2017)
This article offers readers a theological entrée to Wolfgang Amadeus Mozart’s comic opera, Così fan tutte, written in collaboration with Lorenzo da Ponte in 1789. It engages the opera as a means of social and theological criticism. The opera presents Mozart’s understanding of love through a critical engagement with the late Enlightenment and French materialism. While da Ponte’s libretto may well endorse materialism’s attack on the church and on Christian anthropology, Mozart’s music is more ambiguous: on the one hand, it demonstrates the weakness of Baroque Catholicism to withstand the rationalist criticism of the Enlightenment; on the other hand, it exposes the sobering reality which such rationalist materialism itself produces—a reality marked by strained and ultimately impoverished human relationships.